SAFFRON (CROCUS SATIVUS) AMELIORATES TNBS-INDUCED COLITIS IN RATS VIA DOWNREGULATION OF INFLAMMATORY CYTOKINES TNF-α AND IL- 10, CASPASES-3 GENE EXPRESSION AND OXIDATIVE STRESS IN EXPERIMENTAL RATS: Pharmaceutical Science-Pharmacology - ZAFER SAAD ALSHEHRI; WIDAD M. AL-BISHRI; RASHA H. HUSSEIN; MANAL E. EL-HALWAGY (International Journal of Life Science and Pharma Research, 2022)
Ulcerative colitis (UC) is a chronic replacing disorder of the gastrointestinal tract by inflammation and tissue damage. Saffron, a spice derived from the flower of Crocus sativus, is rich in carotenoids . In the current study, we aimed to investigate the potential alleviating effects of Saffron extract against TNBS-induced colitis in rats. saffron extract (80 ml/kg body weight was administered daily by oral gavages in ulcerative colitic rats. Administration of saffron extract mitigated the colonic levels of TNF-a and IL- 10 cytokines. The attenuation of saffron extract to colon injury was also associated with suppression of oxidative stress via reduction of lipid peroxides and nitric oxide along with boosting the antioxidant defenses through restoration of colon glutathione. In addition, caspases-3 gene expression activity, an apoptotic marker, was inhibited. Furthermore, addition of sucrose on the diet of colitic rats increases the colonic inflammation, without incidence on the antioxidant status of colitic rats, indicating that the increase in oxidative stress is directly related to TNBS rather than sucrose.